2017
DOI: 10.7150/thno.20491
|View full text |Cite
|
Sign up to set email alerts
|

11C-Methionine-PET in Multiple Myeloma: A Combined Study from Two Different Institutions

Abstract: 11C-methionine (MET) has recently emerged as an accurate marker of tumor burden and disease activity in patients with multiple myeloma (MM). This dual-center study aimed at further corroboration of the superiority of MET as positron emission tomography (PET) tracer for staging and re-staging MM, as compared to 18F-2`-deoxy-2`-fluoro-D-glucose (FDG).78 patients with a history of solitary plasmacytoma (n=4), smoldering MM (SMM, n=5), and symptomatic MM (n=69) underwent both MET- and FDG-PET/computed tomography (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 29 publications
4
55
0
5
Order By: Relevance
“…The current study conducted in patients with newly diagnosed, treatment-naïve MM confirms the higher sensitivity of 11 C-MET PET/CT, with about 50% of subjects demonstrating more lesions as compared to 18 F-FDG PET/CT, thus being in line with previous preliminary observations [18][19][20]22]. Furthermore, we have investigated for the first time 11 C-MET PET volume-based biomarkers (TMTV, TMLU) demonstrating a positive correlation with MM serum markers of tumor burden such as M component, bone marrow (BM) infiltration, or B2M.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current study conducted in patients with newly diagnosed, treatment-naïve MM confirms the higher sensitivity of 11 C-MET PET/CT, with about 50% of subjects demonstrating more lesions as compared to 18 F-FDG PET/CT, thus being in line with previous preliminary observations [18][19][20]22]. Furthermore, we have investigated for the first time 11 C-MET PET volume-based biomarkers (TMTV, TMLU) demonstrating a positive correlation with MM serum markers of tumor burden such as M component, bone marrow (BM) infiltration, or B2M.…”
Section: Discussionsupporting
confidence: 91%
“…For these reasons, alternative tracers such as 11 C-methionine ( 11 C-MET) [14], 11 C-choline [15], or radiolabeled C-X-C chemokine receptor 4 ligands [16,17] have been investigated. Several studies have suggested a higher sensitivity of 11 C-MET PET/CT over 18 F-FDG PET/CT in the detection of both intra-and extramedullary disease [18,19]. In addition, a better correlation of 11 C-MET uptake with the degree of BM infiltration by malignant PCs has been recently reported [20].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, combinatorial PET scan detected 65% of the lesions seen in newly diagnosed patients, and its detection rate was lower compared with standard low‐dose CT. This percentage is comparable with the detection rate of [ 18 ]F‐FDG PET, which ranges between 60% and 80% . Since the detection of lytic bone lesions is one of the main criteria for starting an anti‐MM treatment, WBCT is currently considered as the standard technique for investigating MM‐induced bone disease of myeloma bone disease.…”
Section: Discussionsupporting
confidence: 53%
“…The Würzburg group has also highlighted the superiority of 11 C-methionine over 18 F-FDG for staging and re-staging of both intra-and extramedullary MM lesions [49,50]. These results were further confirmed in both patient-and lesion-based analyses in the largest so far, dual-center study of 78 patients (4 solitary plasmacytoma, 5 SMM, 69 symptomatic MM) published in 2017 [51]. Moreover, the same group has recently performed the first head-to-head comparison of 11 C-methionine and 11 C-choline for metabolic imaging of MM in 19 patients with a history of MM (n = 18) or solitary bone plasmacytoma (n = 1).…”
Section: C-methioninementioning
confidence: 86%